An investigation Into the impact of student unrests on the University of Pretoria’s organisational climate and academic staff members’ work satisfaction from the perspective of the Self-Determination Theory (SDT) - Maree, David J.F. (University of Pretoria, 2023)
Dissertation (MA (Psychology))--University of Pretoria, 2022.